2014
DOI: 10.5455/ijmsph.2014.150920142
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, awareness and perception of medical college students on rabies and its prevention

Abstract: Background: Rabies continues to be major public health problem in India in-spite of the wide availability of anti rabies vaccine. In India 20,000 dies of rabies annually. The large number of deaths due to rabies can be attributed to people not aware of the various aspects of the disease and its prevention. Aims & Objectives: To assess the knowledge and perception among first year medical college students. Materials and Methods: This study was a descriptive study conducted at Hassan Institute of Medical Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 1 publication
3
11
2
Order By: Relevance
“…14 Praveen et al in their study reported that 48% of medical students knew that hydrophobia and aerophobia are the symptoms of rabies in the human beings. 11 The correct knowledge about fatality of rabies was found in 68.8% of medical students in present study which was near to study done by Praveen et al where 60% of students knew that rabies is 100% fatal. 11 In contrast, Bhalla et al in their study, observed that only 12% of study subjects knew about fatal nature of rabies.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…14 Praveen et al in their study reported that 48% of medical students knew that hydrophobia and aerophobia are the symptoms of rabies in the human beings. 11 The correct knowledge about fatality of rabies was found in 68.8% of medical students in present study which was near to study done by Praveen et al where 60% of students knew that rabies is 100% fatal. 11 In contrast, Bhalla et al in their study, observed that only 12% of study subjects knew about fatal nature of rabies.…”
Section: Discussionsupporting
confidence: 55%
“…11 The correct knowledge about fatality of rabies was found in 68.8% of medical students in present study which was near to study done by Praveen et al where 60% of students knew that rabies is 100% fatal. 11 In contrast, Bhalla et al in their study, observed that only 12% of study subjects knew about fatal nature of rabies. 14 About 46% of medical students knew the correct incubation period of rabies in present study which was near to finding of a study done by Shah et al where this data was 51.7%.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…[7] Shashikantha et al reported that 74% of the study participants were aware of dog bite as the mode of transmission, 68.8% about hydrophobia as a sign of rabies, 62%–72% about the different categories of wounds, and 10%–52% about the various aspects of PrEP and PEP. [8] Chowdhury et al in their study conducted on medical interns have reported that 27.5%–95% were aware of the different categories of wounds, 10%–73.8% about the various aspects of vaccine administration, 10%–85% about the various aspects of immunoglobulin administration, and 60%–77% about the various aspects of wound management.…”
Section: Discussionmentioning
confidence: 99%